Intracellular and extracellular activities of V-domain Ig-containing suppressor of T cell activation (VISTA) modulated by immunosuppressive factors of tumour microenvironment - Abooali, Maryam; Schlichtner, Stephanie; Lei, Xi; Aliu, Nijas; Ruggiero, Sabrina; Loges, Sonja; Ziegler, Martin; Hertel, Franziska; Volckmar, Anna-Lena; Stenzinger, Albrecht; Christopoulos, Petros; Thomas, Michael; et al. (Cancer letters, 2025)
V-domain Ig-containing suppressor of T cell activation (VISTA) is a unique immune checkpoint protein, which was reported to display both receptor and ligand activities. However, the mechanisms of regulation of VISTA activity and functions by factors of tumour microenvironment (TME) remain unclear and understanding these processes is required in order to develop successful personalised cancer immunotherapeutic strategies and approaches. Here we report for the very first time that VISTA interacts with another immune checkpoint protein galectin-9 inside the cell most likely facilitating its interaction with TGF-β-activated kinase 1 (TAK1). This process is required for protection of lysosomes, which is crucial for many cell types and tissues. We found that VISTA expression can be differentially controlled by crucial factors present in TME, such as transforming growth factor beta type 1 (TGF-β) and hypoxia as well as other factors activating hypoxic signalling. We confirmed that involvement of these important pathways modulated by TME differentially influences VISTA expression in different cell types. These networks include: TGF-β-Smad3 pathway, TAK1 (TGF-β-activated kinase 1) or apoptosis signal-regulating kinase 1 (ASK1)-induced activation of activating transcription factor 2 (ATF-2) and hypoxic signalling pathway. Based on this work we determined the five critical functions of VISTA and the role of TME factors in controlling (modulating or downregulating) VISTA expression.